(3GdNUNUI h CKQgG Ydi Mbhb GdYGedjf HGdbWGY GdYGe (B/s - (3MHT, MHT eMeOs ((3HjQhJ(B: s (3efThQGJ GdMdHj(B, s, 2011)
(3eGgjI GdNUNUI h fTCJgG h CgOGagG h OQGSI GdNUNUI ef efXhQ ESdGej , GdGLQGAGJ GddGReI dYedjI GdNUNUI , GdJWhQGJ GdGbJUGOjI h GdNUNUI h GdNUNUI aj GdhWf GdYQHj , GdNUNUI h CKQgG Ydi Mbhb GdYGedjf aj GdbWGY GdYGe (B: (3WHjYI YdGbI GdehXa GdYGe HGdGOGQI GdYGeI , CKQ GdNUNUI Ydi GdYeGdI GdaGFVI h SHd eYGdLJgG h CKQgG Ydi GdMbhb GdeGdjI ddYGedjf HGdbWGY GdYGe (B.s
(3eQGLY U(B.227 (3; eUWdMGJ U(B.250s
Keywords: (3GdTQcGJs; (3GdbWGY GdNGUs; (3GdbWGY GdYGes